COVID-19 and online learning in higher learning institutions: review on issues and challenges faced by students / Ayu Nazurah Dzulhasdi ... [et al.] - Dzulhasdi, Ayu Nazurah; Rosli, Siti Nur Anis Safiah; Tunku Abaidah, YM Tunku Nashril (2021)
Education is one of the sectors that has been impacted by Covid-19 causing the closure of education institutions worldwide. Since then, it is an obstacle for implementing face-to-face teaching and learning process. A major shift is needed from face-to-face teaching and learning to online learning. Online learning is no longer an option but has become a necessity for students during Covid-19. While higher education may have transformed and moved to online on the era of Covid-19, not all students are generally prepared to adapt to the online learning due to some challenges. The main purpose of the paper was to explore the issues and challenges of online learning faced by students in higher learning institutions during Covid-19. This also includes article reviews focusing on current and early reports published once Covid-19 pandemic has become global issue. Results of the review show that the issues and challenges can be classified into four: facilities, technological literacy problem, lack of emotional and psychological support and financial problem.